Green Human Resources Practices and Impact on Possibility of Applying Total Quality Management - Kadhim, Sami Abdullah; Atiyah, Latif Abdulridha (Research Parks Publishers, 2024)
The researcher is definitely working to study the impact dimensions of total quality management (Customer Focus-CF, Continuous Improvement-CI, Employee Participation-EP and Leadership-LE) on dimensions human resources practices (Employee-EM and Hiring-HI). The researcher focused on studying the dimensions of variables to develop production of institutions and improve performance of organizations. The researcher selected a sample of workers at the Central Oil Company / Iraq. In its work, this study adopted a questionnaire form to collect information and data and distribute it to the targeted sample. The number (154) and (7) were incorrect models. Valid questionnaires were obtained (147). The researcher used SPSS & SmartPLS 4 in statistical analysis. Important results and conclusions were obtained, also relying on previous studies. As well as emphasizing institutions to implement comprehensive total quality management to improve performance. The researcher emphasized the support that quality provides to organizations and the recommendations that help in continuous improvement.